The First Business Application: A Significant Milestone in Software History. - Glass, Robert L. (Communications of the ACM, 2005)
The article focuses on the history of computer software and provides information on the first business applications software. The development of the first business applications software has been considered as one of the most significant software milestone of all time. These programs massage business data and produce management-focused reports. The earliest business applications software was developed in 1951, developed by an English company called J. Lyons & Co. The company has not only written the first business software application, but also has built its own computer hardware to run that software. That computer later came to be called the LEO, and it was a business production version of the EDSAC computer developed at Cambridge University. This program includes applications like transaction data processing, sales, and inventory programs. Results of those transactions were compared to pre-set standards, forecasts, and budgets. Variances were identified and dealt with by specifically assigned lower-level managers. What-if explorations requested by senior management could also be undertaken via the software. The result was a real-time approach to management information processing coupled with a decision support system that would be the envy of some companies even today.